Implementation of Prophetic Parenting Strategies to Simulate the Development of Religious and Moral Values in Young Children - Nurmalasari, Nurmalasari; Istiqlaliyah, Hulailah (Kiddie: Early Childhood Education and Care Journal, 2026)
Early childhood is an individual who is experiencing development and growth. Early childhood 0-5 years old has a rapid potential in the formation of morals, therefore it is necessary to have proper care to form good character and morals. One effort that can be done is to apply parenting patterns like the Prophet Muhammad or known as prophetic parenting, such as displaying good role models, finding the right time to provide guidance, being fair and fulfilling children's rights, giving punishment and helping children to be devoted and do obedience. By applying this method, it is hoped that the development of religious and moral values of early childhood is achieved in accordance with Permendikbud No. 137 of 2014 concerning STPPA for ages 4-6 years. The purpose of this study was to determine the application of prophetic parenting in improving the development of religious and moral values of early childhood at PAUDQu Annisa Depok. Researchers conducted observations of teaching and learning activities inside and outside the classroom by observing the behavior of each child. The method used in this study is Qualitative Descriptive, namely direct observation and description. In this study, the techniques used to collect the data needed by the researcher were by means of observation, interviews, and documentation. The results of this study indicate that the school has a program that implements Islamic values and the teachings of the Prophet Muhammad such as the habit of memorizing the Quran, practicing congregational prayer, memorizing daily prayers and hadiths and telling the story of the prophet which are practiced routinely and consistently so that they can improve the development of religious and moral values of early childhood in accordance with STPPA Permendikbud No. 137 of 2014 aged 4-6 years.